Discourse, Politics and Media in Contemporary China - Cao, Qing; Chilton, Paul; Tian, Hailong (John Benjamins Publishing Company, 2014)
After three and a half decades of economic reforms, radical changes have occurred in all aspects of life in China. In an authoritarian society, these changes are mediated significantly through the power of language, carefully controlled by the political elites. Discourse, as a way of speaking and doing things, has become an indispensable instrument for the authority to manage a fluid, increasingly fragmented, but highly dynamic and yet fragile society. Written by an international team of leading scholars, this volume examines socio-political transformations of contemporary Chinese society through a systematic account, analysis and assessment of its salient discourses and their production, circulation, negotiation, and consequences. In particular, the volume focuses on the interplay of politics and media. The book's intended readership is academics and students of Chinese studies, language and discourse, and media and communication studies.